2022
DOI: 10.3390/biology11020261
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Ultrasound Analysis as a Predictive Tool of Ram Sperm Quality

Abstract: Testicular ultrasound is a non-invasive technique that could be very useful for predicting ram seminal quality. Recent software developments allow macroscopic and microscopic evaluation of testicular parenchyma. Thus, the aim of this study was to evaluate the testicular echotexture using ultrasound-video analysis and investigate its possible correlation with semen quality. Nine rams were evaluated for one year using a portable ultrasound scanner and the echotexture was analyzed with ECOTEXT® software. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Acoustic impedance is, in turn, related to the tissue density crossed by the acoustic beam, resulting in a larger (shift toward white in the sonogram) or lesser (shift toward black in the sonogram) echo. Assuming a relationship between pixel intensity and a specific point’s ability to reflect the acoustic beam as a sign of tissue density, several studies have investigated the relationship between the pixel intensity of testicular sonograms, quantified by image-analysis software, and semen quality in domestic animals [ 17 , 18 , 19 , 20 , 21 , 22 ] and humans [ 23 , 24 , 25 , 26 ]. These studies revealed that changes in testicular pixel intensity were correlated with the percentage of morphologically normal live spermatozoa.…”
Section: Grey-scale Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic impedance is, in turn, related to the tissue density crossed by the acoustic beam, resulting in a larger (shift toward white in the sonogram) or lesser (shift toward black in the sonogram) echo. Assuming a relationship between pixel intensity and a specific point’s ability to reflect the acoustic beam as a sign of tissue density, several studies have investigated the relationship between the pixel intensity of testicular sonograms, quantified by image-analysis software, and semen quality in domestic animals [ 17 , 18 , 19 , 20 , 21 , 22 ] and humans [ 23 , 24 , 25 , 26 ]. These studies revealed that changes in testicular pixel intensity were correlated with the percentage of morphologically normal live spermatozoa.…”
Section: Grey-scale Ultrasonographymentioning
confidence: 99%
“…In veterinary medicine, the study of testicular vascularization has been conducted in various animal species, including stallions [ 8 , 81 , 82 , 83 , 84 ], jackasses [ 85 ], tomcats [ 86 , 87 ], bulls [ 17 , 88 , 89 ], rams [ 20 , 90 , 91 ], bucks [ 62 , 92 ], and dogs [ 52 , 65 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. The results of these studies essentially confirm a relationship between testicular arterial blood flow and seminal quality in both normal and pathological conditions.…”
Section: Colour Doppler and Power Dopplermentioning
confidence: 99%
“…Recent ultrasound-video analysis and software developments have allowed the visualization of tissue at the microscopic level. Carvajal-Serna et al [8] revealed that echotexture analysis via ultrasound video could be a valuable tool for assessing the breeding soundness of rams. An increase in the number of white and grey pixels could indicate a decrease in seminal quality, and tubular density and lumen area could be predictors of good seminal quality.…”
Section: Relationship Between Sperm Quality and Fertilitymentioning
confidence: 99%
“…Acoustic impedance is connected to the density of the tissue penetrated by the acoustic beam, leading to a stronger or weaker echo. Multiple studies have explored the correlation between the grayscale intensity values of testicular parenchyma and the quality of semen in domestic animals [ 4 , 22 , 30 , 31 , 32 , 33 ], and humans [ 34 , 35 , 36 , 37 ]. These studies found a correlation between alterations in testicular pixel intensity and the proportion of morphologically normal viable sperm cells.…”
Section: Introductionmentioning
confidence: 99%